Bentonite Powder Catalyzed Synthesis of Coumarins from in situ Generated Stabilized Phosphorus Ylides in Solvent-free Conditions - Ramazani, Ali; Amini, Issa; Massoudi, Abdolhossain (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1 : 1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by phenols (1-hydroxynaphthalene and 2-hydroxynaphthalene) leads to vinyltriphenylphosphonium salts, which undergo aromatic electrophilic substitution reaction with conjugate base to produce corresponding stabilized phosphorus ylides. Bentonite powder was found to catalyze the conversion of the stabilized phosphorus ylides to coumarins in solvent-free conditions at 80–90ºC in 1 h in fairly high yields. Microwave also was found to catalyze the same reactions in the presence of bentonite powder in solvent-free conditions at microwave power 0.18–0.45 KW in 3 min.